Socialization and Digital Marketing Workshop for UMKM in Ngamprah District, West Bandung Regency: Sosialisasi dan Workshop Digital Marketing pada UMKM di Kecamatan Ngamprah Kabupaten Bandung Barat - Rizki Indrawan; Eka Septriarini; Lukni Burhanudin; Marlina Marlina; Aam Rachmat Mulyana (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Currently, the problem of the lack of understanding of SMEs regarding digital promotion in Ngamprah District has resulted in the product being less exposed to the wider community. The purpose of carrying out this activity is so that industrial players in this area can digitize their products without knowing the location so that the wider community can buy products and the effect of course on the ngamprah community itself. The form of activity in community service is the provision of materials offline, namely a team of lecturers from the Faculty of Economics and Business who came directly to Ngamprah District by providing materials related to Digital Marketing to SMEs. Through this activity, a fairly good understanding was obtained from the participants of the socialization and workshop regarding the preparation of digital marketing, social media marketing, the benefits of digital marketing and the use of social media features.